The Human Skeletal Multimedia System / Norhayati Suzari - Norhayati, Suzari (2002)
This project named The Human Skeletal Multimedia System, is a medical web site that applying virtual reality in it presentation. This is an effort to integrate between medicine mystery and computing technology. Within this web site users will be able to explore beneath human muscular and skin, which is human skeletal system. This educational revealing knowledge will be delivered by multimedia interactive elements such as 30 graphics, animation and sounds. As to ensure that this project will fulfill users need to the fullest I have made a literal observation on the current web sites together with interview sessions with target users. Throughout this processes I can estimate users expectation towards the system and perhaps some manipulation from the current system in order to develop a better system.To create an attractive and smooth 30 web site I decided to use the latest creative multimedia software that is 30 Studio Max and VRML (Virtual Reality Modeling Language) as the medium to present my 30 world to users. I also include sound effects to this web site to add the realism of the virtual world. As for now, that's what I can assume and promised to users about this project.Hop fully, it will contribute to the growth of computer graphic technology and our local medical website.